1996
DOI: 10.1128/jb.178.7.1793-1799.1996
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gene coding for GDP-mannose dehydrogenase (algD) from Azotobacter vinelandii

Abstract: Azotobacter vinelandii presents a differentiation process leading to the formation of desiccation-resistant cysts. Alginate, the exopolysaccharide produced by this bacterium, has been postulated to have a role in cyst formation. Here, we report the cloning and characterization of the A. vinelandii gene coding for the enzyme GDP-mannose dehydrogenase (algD), which is the key enzyme for alginate synthesis in Pseudomonas aeruginosa. This gene has a high degree of similarity with the algD gene from P. aeruginosa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 41 publications
4
106
1
Order By: Relevance
“…After completion of this process, the cells are at a resting stage designated cyst, and in these cysts the cells are surrounded by a rigid coat consisting of layers (intine and exine) in which alginate is a major component. As expected, mutants unable to produce alginate also fail to form cysts (6).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…After completion of this process, the cells are at a resting stage designated cyst, and in these cysts the cells are surrounded by a rigid coat consisting of layers (intine and exine) in which alginate is a major component. As expected, mutants unable to produce alginate also fail to form cysts (6).…”
mentioning
confidence: 87%
“…All genes involved in bacterial alginate biosynthesis, except algC (20), are clustered on the chromosome and are transcribed in one or several units (6,8,34,36). Polymerization of the sugar monomers takes place in the cytoplasmic membrane, using GDP-mannuronic acid as a precursor.…”
mentioning
confidence: 99%
“…The A. vinelandii biosynthetic pathway has been shown previously to be identical to that found in Pseudomonas aeruginosa and many of the genes are conserved (Fialho et al, 1990 ;Gacesa, 1998 ;Rehm et al, 1996). The transcriptional activation of the GDP-mannose dehydrogenase gene (algD) is a key point in pathway regulation (Campos et al, 1996) and is mediated by the alternative sigma factor AlgU, a homologue of RpoE (MartinezSalazar et al, 1996). Recently it was shown that A. vinelandii strain UW136 has a natural insertion element in the algU gene , which may explain the alginate-minus phenotype of strains derived from UW.…”
Section: -4101 # 2001 Sgmmentioning
confidence: 99%
“…The mature cysts are surrounded by two capsule-like layers containing a high proportion of the exopolysaccharide alginate. This exopolysaccharide is essential for the encystment process, since nonmucoid strains fail to encyst (Campos, et al, 1996). In Azotobacter vinelandii, alginate protects nitrogenase from oxygen and increases nitrogen fixation (Sabra, et al, 2000).…”
Section: Exopolysaccharide Productionmentioning
confidence: 99%